2016
DOI: 10.2147/amep.s101395
|View full text |Cite
|
Sign up to set email alerts
|

Quality improvement teaching at medical school: a student perspective

Abstract: Guidelines in the UK require all doctors to actively take part in quality improvement. To ease future doctors into the process, formal quality improvement teaching can be delivered during medical school.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 4 publications
1
21
0
Order By: Relevance
“…Incorporating formal teaching on quality of care in medical schools provides an expansive platform to ensure that future physicians learn about quality improvement, how to think about continuously incorporating quality initiatives into their work, and ultimately improve quality of care and patient outcomes. 4 , 15 …”
Section: Discussionmentioning
confidence: 99%
“…Incorporating formal teaching on quality of care in medical schools provides an expansive platform to ensure that future physicians learn about quality improvement, how to think about continuously incorporating quality initiatives into their work, and ultimately improve quality of care and patient outcomes. 4 , 15 …”
Section: Discussionmentioning
confidence: 99%
“…Students who completed the reported graduating with skills and knowledge in clinical audit and quality improvement which they translated into practice after graduation enabling them to measure and improve their own and others’ practice. Previous studies have shown that using clinical audit as a teaching tool for both medical students and residents can lead to short-term improvements in patient care 9 - 11 and educational outcomes 12 - 14 …”
Section: Discussionmentioning
confidence: 99%
“…The impact of an intervention bundle on blood culture contamination rate Compliance with the World Health Organisation checklist in image-guided procedures Delivery of pain management for patients after major gynaecological surgery QI teaching in universities is hampered by competing priorities within medical curricula and a lack of faculty teaching capacity [11,12]. Theory-based teaching from senior QI experts can seem irrelevant and insignificant when compared to the major priority of students and educatorsdeveloping the clinical knowledge and skills needed to succeed as a doctor.…”
Section: Introductionmentioning
confidence: 99%